Management of Patients with Graves' Disease and Orbital Involvement: Role of Spectral Domain Optical Coherence Tomography. (18th February 2018) - Bruscolini, Alice; La Cava, Maurizio; Gharbiya, Magda; Sacchetti, Marta; Restivo, Lucia; Nardella, Chiara; Marenco, Marco; Lambiase, Alessandro
Abstract : Purpose . To investigate the role of choroidal thickness evaluation with spectral domain optical coherence tomography (SDOCT) and enhanced depth imaging (EDI) technique in the management of patients with Graves' disease and orbitopathy (GO). Methods . Thirty-six eyes of 18 patients with GO and 36 eyes of 18 age-matched control subjects were included in this retrospective observational study. All the subjects underwent a complete ophthalmological evaluation, including clinical activity score (CAS) and exophthalmometry. The SDOCT images of the choroid were obtained by EDI modality. Results . Choroidal thickness was significantly increased in GO than in control eyes (p < 0.01 ). A significant correlation was found between choroidal thickness and CAS, proptosis, and the duration of disease (p < 0.05 ). Conclusion . This study shows that choroidal thickness, evaluated with EDI-OCT, is significantly increased in patients with GO and correlates with the activity of the disease, proptosis, and duration of the disease. The choroidal thickening may reflect the ocular hemodynamic changes, and enhanced depth imaging optical coherence tomography may be a useful tool for the evaluation of orbital congestion and management of patients with Graves' disease and orbital involvement.